Phase Transition in Pyrolyzed Samples of Natural Silk (Texas Journal of Multidisciplinary Studies, 2022)
The article discusses the use of non-recyclable fibrous waste of natural silk as electrically conductive materials for special purposes. The dependence of the electrical conductivity of powdered samples of natural silk on the heat treatment temperature is shown. A phase transition is described, in particular, the "metal-dielectric" transition in pyrolyzed samples of natural silk.